电动汽车动力驱动装置 (2019)
本发明提供种电动汽车动力驱动装置，包括空心轴电机、变速器和差速器，电机的空心齿轮轴通过花键联接输入齿轮轴将动力传递给传动系统，输出齿轮与差速器连为体，两个半轴通过花键与差速器联动，短半轴直接与车轮相连，长半轴穿过电机的空心齿轮轴联接车轮。本发明所提供的电动汽车体化驱动动力总成能有效减小体积以及各部件之间的装配误差，调节系统振动特性，提高系统传动效率。 The invention provides a power driving device of an electric automobile. The device comprises a hollow-shaft motor, a gear box, and a differential, a hollow gear shaft of the motor is connected to an input gear shaft through a spline to transfer power to a transmission system, an output gear and the differential are connected to an integral body, two axle shafts and the differential are connected through a spline, a short axle shaft is connected with a wheel, and a long axle shaft penetrates through the hollow gear shaft of the motor and is connected with the wheel. According to the integrated driving power assembly of the electric automobile, the size and the assembling error between parts can be effectively reduced, the system vibration characteristics are adjusted, and the system transmission efficiency is improved.